EXPERIENCE GAINED IN CULTIVATING INDUSTRIAL JOJOBA IN THE ENVIRONMENTS OF TURKMENISTAN - A. M. Penjiyev (Труды по прикладной ботанике, генетике и селекции)
Background. Studying the possibilities of jojoba cultivation for the development of the Kara-Kum Desert, improvement of the feeding  reserves in pastures, quick sand fixation, and production of bioactive  compounds for the medical and cosmetic industries is a vital problem.Results and conclusion. Biotechnological features, origin and  distribution of the crop, the properties and structure of oil from  jojoba fruits are described. Empirical dependences have been found  under the conditions of a solar hothouse from the produced  equations of thermal and material balances in temperature,  humidity, and evaporation from a water or soil surface in 10-days  periods within a year. On the basis of experimental data and  calculation results, is may be ascertained that it is possible to  cultivate jojoba in the environments of an arid ecosystem in  Turkmenistan. The introduction of this new valuable crop is very  important to the national economy, and may help to develop deserts,  expand the feeding reserves for animals, and produce useful raw materials for many industries.